The Relationship Between Predisposing Factors and The Incidence of Chronic Suppurative Otitis Media - Nayoan, Christin Rony; Maharani , Arum; Towidjojo, Vera Diana; Syamsi, Nur (Fakultas Kedokteran, Universitas Palangka Raya, 2025)
One of the health problems in Indonesia is hearing loss which can be caused by otitis media. The incidence of Chronic Suppurativa Otitis Media (CSOM) in the world ranges from 65-330,000,000 per year. Research shows that in 2020, in the ENT Clinic at Anutapura General Hospital, recorded 289 out of 506 patients seeking treatment for ear problems, making it the most cases compared to nose and throat problems. Predisposing factors for CSOM include nutritional status, immunity, history of Acute Otitis Media (AOM), history of Acute Respiratory tract Infection (ARI), exposure to cigarette smoke and nutritional status.The objective of this study is to determine the relationship between predisposing factors and the incidence of CSOM in the ENT clinic at Undata General Hospital, Central Sulawesi. This study was a cross-sectional analytic observational study conducted at the ENT clinic of Undata General Hospital, Central Sulawesi. Sampling was done using purposive sampling technique by setting certain criteria. Participants were asked to fill out a questionnaire that could help researchers identify possible risk factors for CSOM to collect primary research data. Data analysis in this study used bivariate data analysis to test the relationship between two variables. Based on the results of bivariate analysis using the chi-square test, the p-value of the factors studied was 0.299 for immune status, 0.35 for genetic factors, 0.04 for history of ARI, 0.000 for history of AOM, 1.000 for cigarette smoke exposure, 0.792 for nutritional status, 0.045 for age and 0.193 for gender. Conclusion of this study, predisposing factors that are significantly associated with the incidence of CSOM in the ENT clinic of Undata general hospital are history of ARI, history of AOM and age.